Reflections on Conducting Field Research on Women in Polarised Post-Conflict Communities in Plateau State, Nigeria - Bulus, Kwopnan Ibrahim Bulus; Maza, Kangdim Dingji Maza; Bulus, Judith Gampimwa Bulus; Dimang, Rotkang Roseline Dimang; Maigari, Anna Matlong Maigari (African Journal of Stability and Development (AJSD), 2024)
Due to the fragile nature of peace in polarised post-conflict communities, conducting qualitative phenomenological research on women in such communities is not easy for researchers. Consequently, conducting fieldwork in such a location requires adequate and thorough planning before proceeding to the field. In this article, the authors shared their common experiences of conducting research on women in polarised post-conflict communities. This article emphasised on the need for a researcher to establish multiple initial contacts with persons in the research locations, Civil Society Organisations (CSOs), and/or Non-Governmental Organisations (NGOs) that have done some work or are currently working in the locations. The contacts can provide useful insights about the nature of the research locations, the potential participants, and the sensitivities. The article shows that when conducting interviews and Focused Group Discussions (FGDs), the researcher should ensure the safety of both the researcher and the participants by choosing suitable times and safe locations. The article emphasised the need to ensure that ethical considerations should guide the research process. The researcher, in conducting the fieldwork, must ensure that continuous informed consent is obtained from the participants in the research process. This will ensure that the researcher “does no harm” to the participants. Trust building through confidentiality and anonymity should be guaranteed to the participants to build rapport to ensure their full participation.